Nanoelectronics and Photonics - Korkin, Anatoli (Springer, 2017)
Nanoelectronics and Photonics: From Atoms to Materials, Devices, and Architectures provides a description of the core elements and challenges of advanced and future information technology. By linking the materials physics and chemistry at the atomic scale with device and circuit design and performance requirements, tutorial chapters from leaders in the field present a coherent picture of theoretical and experimental research efforts and technology development in this highly interdisciplinary area. Short visionary articles by Nicolaas Bloembergen, Nobel Laureate in Physics (1981), Konstantin Likharev, distinguished professor at Stony Brook University, and Stanley Williams, senior fellow and director of the Quantum Science Research group at Hewlett-Packard, offer unique perspectives and insights. Nanoelectronics and Photonics is essential reading for researchers and graduate students in materials science, device physics, and electrical and computer engineering.